Inventory and Pest Attack Rate on Sugar palm Plantation (Arenga pinnata Merr.) in Limapuluh Kota Regency, Indonesia - Ananta Febriansyah; Ujang Khairul; Zahlul Ikhsan (CIB Nusantara, 2025)
Sugar palm (Arenga pinnata Merr.) has long been used as a raw material for industry and food. However, the productivity of sugar palm plants is often limited by pest infestation. This study aims to obtain data on the type and level of pest attacks that graze sugar palm plants on people's plantation land in Limapuluh Kota Regency. The survey method was applied in three sub-districts using purposive random sampling to select sugar palm plants that are more than five years old. Observations show that there are four main types of pests of sugar palm plants, namely horn beetles (Oryctes rhinoceros L.), sago beetles (Rhynchophorus sp.), bats (Chiroptera), and ferrets. The highest percentage of attacks on horn beetle pests with an average of 68.88%, while the lowest is the sago beetle with an average of 6.66%. This study suggests proper pest control in sugar palm plants to maintain the productivity of sugar palm plants.